In vitro anti-snake venom activities of aloysia citriodora palau : new possibilities for a known aromatic plant - Cáceres, Marcela I. (2017)
Fil: Cáceres, Marcela I. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.